2015
DOI: 10.1152/jn.00275.2015
|View full text |Cite
|
Sign up to set email alerts
|

Network effects of deep brain stimulation

Abstract: The ability to differentially alter specific brain functions via deep brain stimulation (DBS) represents a monumental advance in clinical neuroscience, as well as within medicine as a whole. Despite the efficacy of DBS in the treatment of movement disorders, for which it is often the gold-standard therapy when medical management becomes inadequate, the mechanisms through which DBS in various brain targets produces therapeutic effects is still not well understood. This limited knowledge is a barrier to improvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 175 publications
4
41
0
1
Order By: Relevance
“…In addition to these two promising drugs, there are also some new perspectives concerning DBS (Wichmann and DeLong, 2016). Indeed, it has been claimed that understanding how DBS could affect multiple cortical regions downstream, would be an important advance in its use as a therapeutic approach (Alhourani et al, 2015). Understanding also the network effects of DBS will allow tailoring the treatment based on biomarkers related to those effects.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In addition to these two promising drugs, there are also some new perspectives concerning DBS (Wichmann and DeLong, 2016). Indeed, it has been claimed that understanding how DBS could affect multiple cortical regions downstream, would be an important advance in its use as a therapeutic approach (Alhourani et al, 2015). Understanding also the network effects of DBS will allow tailoring the treatment based on biomarkers related to those effects.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Deep brain stimulation (DBS) is clinically used to treat various neurological and neuropsychiatric conditions [1,2], yet despite its widespread use, its mechanisms of action are not fully understood [3e5]. The effects of DBS in humans are often studied using noninvasive functional imaging [6,7]: H 2 O 15 positron emission tomography (PET) [8,9] and functional magnetic resonance imaging (fMRI) [10e13]. These imaging techniques measure changes in hemodynamics caused by DBS in various brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Three potential mechanisms of HFS on neuronal activity have been proposed: inhibition, excitation, and modulation. Studies have shown that HFS may suppress neuronal firing by activation of the inhibitory synapses of neural circuits (Alhourani et al, 2015), or by depletion of the neurotransmitters of excitatory synapses (Iremonger et al, 2006). However, other studies that involved animal experiments and mathematical simulations have shown that HFS may increase the firing rate of neuronal action potentials (Deniau et al, 2010).…”
Section: Introductionmentioning
confidence: 99%